Heat- and PIP2-dependent TRPM4 activity underlies mutually exclusive human diseases - Yuhua Tian; Soohyeon Bae; Xuesong Wu; Kyle C. Rouen; Adriana Hernández-González; Yanxiao Han; Abdullah Al Tekreeti; Simon Vu; Irene Chen; Ellen Li; Igor Vorobyov; Vladimir Yarov-Yarovoy; et al. (Proceedings of the National Academy of Sciences, 2026)
Temperature-sensitive transient receptor potential melastatin subfamily 4 (TRPM4) ion channels convert intracellular calcium increases into membrane depolarization, thereby linking these two powerful cellular signaling pathways in diverse physiological processes. TRPM4 mutations cause severe human hereditary cardiovascular and skin diseases; mysteriously, while these mutations are gain-of-function in nature, they affect the heart and the skin in a mutually exclusive manner. Here, we show that phosphatidylinositol 4,5-bisphosphate (PIP2) lipid is a required cofactor for TRPM4 activity by tightly regulating its calcium sensitivity. We detected two PIP2 binding sites and located the high-affinity site adjacent to the S4-S5 linker. We demonstrated that skin disease–associated TRPM4 mutations relieve the tight control of PIP2, resulting in elevated channel activity but only at the body surface temperature. In contrast, heart diseases are associated with mutations known to boost the number of channels, an effect we found to be annihilated by channel desensitization outside the body core. Indeed, dendritic cells from transgenic mice carrying a skin disease mutant exhibited elevated migration at 25-to-30°C range compared to those from normal mice, but no difference was observed at 37°C. These findings shed light on a molecular mechanism for dynamic regulation of cellular signaling in physiology and diseases.